2012
DOI: 10.1111/j.1468-2397.2012.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among women who were sexually abused as children

Abstract: One of the aims of the study was to investigate how participants in self‐help groups (SHG) for women (n = 87) who had been sexually abused in childhood rated their mental health and to what extent they were at risk of developing posttraumatic stress disorder (PTSD). A further aim was to investigate the relationship between the ratings of mental health, occurrence of PTSD, women's interpersonal relationships, reasons for participating in an SHG and characteristics of the childhood sexual abuse (CSA). The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…The quantitative studies demonstrate the centrality of shame, finding the presence of shame mediated a range of psychological outcomes, including the effectiveness of group psychotherapy on reducing PTSD symptoms (Ginzburg et al, ), sexual revictimisation in adulthood (Kessler & Bieschke, ) and body surveillance and alexithymia (Watson, Matheny, Gagné, Brack, & Ancis, ). Additionally, associations, were found between: shame and suicidal ideation (Kealy, Spidel, & Ogrodniczuk, ; Milligan & Andrews, ; You, Talbot, He, & Conner, ), self‐harming behaviours (Milligan & Andrews, ), dissociation (Talbot, Talbot, & Tu, ), body related trauma (Dyer, Feldman, & Borgmann, ), poor mental health (Rahm, Renck, & Ringsberg, ) and anxiety and depressive symptoms (Willie et al, ). CSA‐related shame also significantly correlated with HIV‐related shame (Willie et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative studies demonstrate the centrality of shame, finding the presence of shame mediated a range of psychological outcomes, including the effectiveness of group psychotherapy on reducing PTSD symptoms (Ginzburg et al, ), sexual revictimisation in adulthood (Kessler & Bieschke, ) and body surveillance and alexithymia (Watson, Matheny, Gagné, Brack, & Ancis, ). Additionally, associations, were found between: shame and suicidal ideation (Kealy, Spidel, & Ogrodniczuk, ; Milligan & Andrews, ; You, Talbot, He, & Conner, ), self‐harming behaviours (Milligan & Andrews, ), dissociation (Talbot, Talbot, & Tu, ), body related trauma (Dyer, Feldman, & Borgmann, ), poor mental health (Rahm, Renck, & Ringsberg, ) and anxiety and depressive symptoms (Willie et al, ). CSA‐related shame also significantly correlated with HIV‐related shame (Willie et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on a community sample, Rahm et al, () quantitative study of psychological distress among women sexually abused as children, recruited from self‐help groups, found feelings of shame, but not guilt, correlated with poor mental health. Talbot et al, () in a clinical sample of 99 women with and without a history of CSA accessing psychiatric services, found that higher levels of shame proneness is associated with higher levels of dissociation, especially among women who had experienced CSA.…”
Section: Discussionmentioning
confidence: 99%
“…Women with obstetric fistula are socially stigmatised and marginalised, psychologically affected and economically deprived, and often suffer a traumatic birth experience [911]. These situations are correlated with mental health problems [1214].…”
Section: Introductionmentioning
confidence: 99%
“…Obstetric fistula associated with mental health problems is one of the most burdensome diseases among women in their early productive years. Studies in low-income countries, including Ethiopia, report that women with fistula have a significantly higher incidence of symptoms of depression, psychosocial dysfunction and anxiety [11, 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation